2019
DOI: 10.1089/dia.2019.0212
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin Improves Erythropoiesis in Diabetes Patients with Anemia of Chronic Kidney Disease

Abstract: Background: We evaluated the erythropoietic effects of canagliflozin, a sodium-glucose cotransporter 2 inhibitor, in type 2 diabetes patients with anemia of chronic kidney disease.Methods: Nine diabetes patients were enrolled and administered 100 mg canagliflozin once a day for 12 weeks. The patients received fixed doses of conventional antidiabetic drugs and renin-angiotensin system inhibitors for 8 weeks before enrollment; these drugs were continued during the study. Endpoints were changes in erythropoiesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 35 publications
5
64
1
3
Order By: Relevance
“…In a small study (9 T2DM patients), canagliflozin 100 mg/day for 12 weeks led to a significant decrease in median ferritin levels (from 72 to 55 ng/mL, p = 0.003). 142 Furthermore, serum ferritin concentrations were significantly and progressively lowered from baseline to 3 and 6 months (from 184.9 to 143.8 and 117.3 ng/mL, respectively, p < 0.05) in 35 canagliflozin (100 mg/day)-treated NAFLD patients. 143 Similar results were also reported in T2DM patients with biopsy-proven NASH.…”
Section: Introductionmentioning
confidence: 84%
“…In a small study (9 T2DM patients), canagliflozin 100 mg/day for 12 weeks led to a significant decrease in median ferritin levels (from 72 to 55 ng/mL, p = 0.003). 142 Furthermore, serum ferritin concentrations were significantly and progressively lowered from baseline to 3 and 6 months (from 184.9 to 143.8 and 117.3 ng/mL, respectively, p < 0.05) in 35 canagliflozin (100 mg/day)-treated NAFLD patients. 143 Similar results were also reported in T2DM patients with biopsy-proven NASH.…”
Section: Introductionmentioning
confidence: 84%
“…Sodium-glucose co-transporter 2 (SGLT2) inhibitors are a newly approved class of oral hypoglycemic agents that increase the excretion of glucose in the urine by inhibiting the reabsorption of urine glucose in the proximal tubules of the kidney, thereby reducing blood glucose levels, weight and blood pressure (Polidori et al, 2014;Inagaki et al, 2015). In addition, SGLT2 inhibitors also have a protective effect on the kidney (Xu et al, 2017) as evidence has shown that after treatment with SGLT2, hemoglobin levels are increased (Maruyama et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…106 As discussed above, the SGLT2 inhibitors canagliflozin and dapagliflozin have been shown to improve anemia in patients with type 2 diabetes and anemia of CKD. 39,40 In a small Japanese study, canagliflozin was associated with significant increases from baseline in serum erythropoietin levels after 2 and 4 weeks, as well as increases in hemoglobin, hematocrit, and RBCs after 12 weeks of treatment. 39 The improvement in erythropoiesis with canagliflozin was independent of changes in other parameters, including blood pressure, body weight, and glycated hemoglobin.…”
Section: Other Therapeutic Agents In Developmentmentioning
confidence: 99%
“…38 Of note, antidiabetic therapy with sodium-glucose cotransporter 2 inhibitors (canagliflozin or dapagliflozin) has been shown to improve hemoglobin levels, as well as glycemic control, in patients with type 2 diabetes and anemia of CKD. 39,40 Although the mechanisms underlying the increase in hemoglobin levels with SGLT2 inhibitors are not fully understood, they are likely to include suppression of hepcidin and stimulation of erythropoiesis. 40…”
Section: Management Of Anemia Of Ckd In Patients With Diabetesmentioning
confidence: 99%